Income tax withholding for Indonesian workers abroad: An observation analysis - Hasan, Hasan; Tarmidi, Deden; Akbar, Taufik (WIM Solusi Prima, 2024)
This study aims to analyze the aspects of taxation on the income of Indonesian workers abroad, both in terms of policy and implementation. The research was conducted with a qualitative approach using the literature method on income tax rules for taxpayers abroad, as well as the interview method to 5 informants of Indonesian workers abroad about the implementation of these rules on the income earned by the informants. Regulators in Indonesia have issued Minister of Finance Regulation No. 18 of 2021, Income Tax Law article 24, and Tax Harmonization Law which regulates the taxation status of overseas workers. The results of interviews from informants explain that the majority of Indonesian workers lack understanding of taxation rules on tax status and income tax withholding processes based on Indonesia’s tax rule or tax rules in the country where the informant works. This result can be an input for Indonesian regulators in optimizing the process of socialization and tax education for Indonesian workers who will and are working abroad.